2009
DOI: 10.2527/jas.2008-0919
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Pediococcus acidilactici or Saccharomyces cerevisiae boulardii modulates development of porcine mucosal immunity and reduces intestinal bacterial translocation after Escherichia coli challenge1,2

Abstract: In this study, the influence of the probiotics, Pediococcus acidilactici (PA) and Saccharomyces cerevisiae boulardii (SCB), on intestinal immune traits and resistance to enterotoxigenic Escherichia coli (ETEC) infection was evaluated in pigs. Two weeks before farrowing, 30 sows and their future litters were allocated to the following treatments: 1) control group without antibiotic or probiotic treatment (CTRL), 2) control with antibiotic (tiamulin) added to weanling feed (ABT), or litters treated with 3) PA, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 67 publications
6
60
1
1
Order By: Relevance
“…It was isolated in France from natural-pasture Gramineae, initially for use in the animal feed industry. The strain has been extensively used as a probiotic in a number of commercial products for pigs, poultry, and aquaculture and eventually for human dietary supplements (2,3,4).…”
mentioning
confidence: 99%
“…It was isolated in France from natural-pasture Gramineae, initially for use in the animal feed industry. The strain has been extensively used as a probiotic in a number of commercial products for pigs, poultry, and aquaculture and eventually for human dietary supplements (2,3,4).…”
mentioning
confidence: 99%
“…Several studies have shown that weaned piglets experienced diarrhoea and poor growth performance when orally challenged with the enterotoxigenic Escherichia coli (ETEC) strain within a short period following weaning (Liu et al, 2013;Bontempo et al, 2014). Lee et al (2012) also observed reduced growth performance and diminished faecal consistency, as well as increased inflammatory response, in piglets challenged by ETEC within 14 days following weaning (Lessard et al, 2009). In this study, the injections of E. coli on days 21 and 25 reduced the gain-to-feed ratio during the three weeks post-challenge, which may indicate that E. coli challenge (double inoculations in older piglets) can induce negative effects on piglets' growth performance even after their gut microbial environment has matured.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies looking at the role of probiotics in pigs have been published (Bomba et al, 2002;Konstantinov et al, 2008;Bird et al, 2009;Lessard et al, 2009;Martin et al, 2009;Pieper et al, 2009;Szabo et al, 2009;Wang et al, 2009), it is very difficult to perform any meaningful metanalysis as the organisms, strains, doses and duration of the experiments are so varied, not to mention the confusing effects of husbandry, environment and genotype on the immune system and microbiota of the animals being studied. Certainly, it would be desirable to compare different probiotics and to follow the piglets through the weaning phase in wellcontrolled large-scale experiments.…”
Section: Do Probiotics Work? -An Overviewmentioning
confidence: 99%